Compare The Effectiveness of Emotion Regulation and Resilience Training on Psychological Well-Being of Mothers of Students with Intellectual Disability - Hamed Moradikia; Fariba Sattarpour Iranaghi; Soniya Emamgholian (Iranian Association of Health Education and Health Promotion, 2017)
Background and Objective: Mentally-disabled children cause many psychological problems in family members, especially in mothers. Due to the importance of psychological well-being of mothers in family and society; the aim of this study was to compare the effectiveness of emotion regulation and resilience training on psychological well-Being of mothers of students with intellectual disability. Methods: In this quasi-experimental study (pre-test and post-test), 30 mentally retarded students were selected in Arak, they were non-randomly divided into two experimental groups (15 people). The exertion training and resilience training were received for the first group (weekly two sessions one and a half hours) and the second group (weekly two sessions per hour), respectively. Prior and after the training, the subjects completed psychological well-being scale (an 84-question form). Univariate and multivariate analysis of covariance (ANCOVA & MANCOVA) was used to analyze the data. Results: The results showed that the mean scores of psychological well-being variable and components increased in the resilience training group (post-stage) in comparison to the emotion regulation training group (P < 0.05).,  Theeffect amount of 68/0  and 26/0 were reported as the maximum and the minimum difference in the two groups in the Autonomous component .   Conclusion: The results indicated that resilience and emotion regulation training, improved psychological well-being of mothers with mentally retarded children.